2014
DOI: 10.1523/jneurosci.5119-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

DAPK1–p53 Interaction Converges Necrotic and Apoptotic Pathways of Ischemic Neuronal Death

Abstract: Necrosis and apoptosis are two distinct types of mechanisms that mediate ischemic injury. But a signaling point of convergence between them has yet to be identified. Here, we show that activated death-associated protein kinase 1 (DAPK1), phosphorylates p53 at serine-23 (pS 23 ) via a direct binding of DAPK1 death domain (DAPK1DD) to the DNA binding motif of p53 (p53DM). We uncover that the pS 23 acts as a functional version of p53 and mediates necrotic and apoptotic neuronal death; in the nucleus, pS 23 induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 36 publications
0
88
2
1
Order By: Relevance
“…However, the expression of exogenous p53 in the p53 −/− neurons alone in the absence of constitutively active DAPK1 (cDAPK1) does not cause apoptosis, showing that pS23 is an essential substrate of cDAPK1. Recently, Pei et al found that activated DAPK1 phosphorylates p53 at serine-23 (pS23) via a direct binding of DAPK1 death domain (DAPK1DD) to the DNA-binding motif of p53 (p53DM), converging the signaling point of necrotic and apoptotic pathways in stroke [53]. They verified that the pS23 was located in both the mitochondria and the nucleus in the cultured cortical neurons.…”
Section: Dapk1 and P53mentioning
confidence: 94%
“…However, the expression of exogenous p53 in the p53 −/− neurons alone in the absence of constitutively active DAPK1 (cDAPK1) does not cause apoptosis, showing that pS23 is an essential substrate of cDAPK1. Recently, Pei et al found that activated DAPK1 phosphorylates p53 at serine-23 (pS23) via a direct binding of DAPK1 death domain (DAPK1DD) to the DNA-binding motif of p53 (p53DM), converging the signaling point of necrotic and apoptotic pathways in stroke [53]. They verified that the pS23 was located in both the mitochondria and the nucleus in the cultured cortical neurons.…”
Section: Dapk1 and P53mentioning
confidence: 94%
“…2,3 To define a promising target that allows a delayed intervention being clinically effective against stroke, we searched for cell death signals downstream of DAPK1. We identified a direct binding of DAPK1 to a DNA-binding motif (DM) of the tumor suppressor protein p53 (p53DM), which is known as a transcriptional regulator of genes that control cell necrosis and apoptosis.…”
Section: +mentioning
confidence: 99%
“…[4][5][6][7] We thus synthesized a membrane-permeable p53DM peptide consisting of amino acid 271 to 282 (Tat-p53DM) that specifically blocked DAPK1-p53 interaction. 3 Activation of DAPK1 phosphorylates p53 at serine-23 (pS 23 ) in the cultured cortical neurons. 3 In the nucleus, the pS 23 induces expression of the proapoptotic genes such as Bax, whereas in the mitochondrial matrix, the pS 23 interacts with a necrotic factor of cyclophilin D. Application of Tat-p53DM effectively blocks these dual pathways of the pS 23 actions in the cortical cultures in vitro, 3 suggesting that Tat-p53DM could be clinically effective against stroke.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations